\(\sqrt{13\sqrt{6\sqrt{4+\sqrt{9-4\sqrt{12}}}}}\)
Rút gọn
a) \(\sqrt{13+6.\sqrt{4+\sqrt{9-4\sqrt{2}}}}\)
b) (\(\frac{x-\sqrt{x}}{\sqrt{x}-1}\)+ 2) .( 2- \(\frac{\sqrt{x}+x}{1+\sqrt{x}}\))
bài 1: Tìm ĐKXĐ (nếu cần) và giải các phương trình sau:
a/ \(\sqrt{3x^2}-\sqrt{12}=0\)
b/ \(\sqrt{\left(x-3\right)^2}=9\)
c/\(\sqrt{4x^2+4x+1}=6\)
d/\(\sqrt{16x-16}-\sqrt{9x-9}+\sqrt{4x-4}+\sqrt{x-1}=8\)
e/ \(\sqrt{1-x}+\sqrt{1-2x}=\sqrt{x+4}\)
Tính:
A=\(\sqrt{4+2\sqrt{3}}-\sqrt{4-2\sqrt{3}}\)
B=\(\sqrt{9-4\sqrt{5}}+\sqrt{9+4\sqrt{5}}\)
C=\(\sqrt{4-\sqrt{7}}-\sqrt{4+\sqrt{7}}\)
D=\(\sqrt{5\sqrt{3+5\sqrt{48-10\sqrt{7+4\sqrt{3}}}}}\)
E=\(\left(4+\sqrt{15}\right)\left(\sqrt{10}-\sqrt{6}\right)\sqrt{4-\sqrt{15}}\)(2 cách)
F=\(\dfrac{\sqrt{17-12\sqrt{2}}}{\sqrt{3-2\sqrt{2}}}-\dfrac{\sqrt{17}+12\sqrt{2}}{\sqrt{3+2\sqrt{2}}}\)
Giải phương trình sau:
a)\(\sqrt{3}.x-\sqrt{12}=0\)
b)\(\sqrt{2}.x+\sqrt{2}=\sqrt{8}+\sqrt{18}\)
c)\(\sqrt{5}.x^2-\sqrt{20}=0\)
d)\(\sqrt{x^2+6x+9}=3x+6\)
e)\(\sqrt{x^2-4x+4}-2x+5=0\)
f)\(\sqrt{\dfrac{2x-3}{x-1}=2}\)
g) \(\dfrac{\sqrt{2x-3}}{\sqrt{x-1}}=2\\\)
Rút gọn:
a, \(\sqrt{\dfrac{4}{9-4\sqrt{5}}}\) -\(\sqrt{\dfrac{4}{9+4\sqrt{5}}}\)
b, \(\dfrac{\sqrt{8-4\sqrt{3}}}{\sqrt{2}}\)
c, \(\sqrt{14-8\sqrt{3}}\)-\(\sqrt{24-12\sqrt{3}}\)
d, \(\sqrt{2-\sqrt{3}}\)\(\times\)\(\left(\sqrt{5}+\sqrt{2}\right)\)
Mỗi khẳng định sau đúng hay sai? Vì sao?
a) \(0,01=\sqrt{0,0001};\)
b) \(-0,5=\sqrt{-0,25};\)
c) \(\sqrt{39}< 7\) và \(\sqrt{39}>6;\)
d) \(\left(4-\sqrt{13}\right).2x< \sqrt{3}\left(4-\sqrt{13}\right)\Leftrightarrow2x< \sqrt{3}.\)
Giải phương trình sau:
6x-3√3x-6=12
bài 1 : giải pt
a,\(\sqrt{\dfrac{2x^2-4x+2}{6}}=1\)
b, \(\dfrac{6}{x-4}=\sqrt{2}\)
c,\(\sqrt{\dfrac{20}{2x^2-8x+8}}=\sqrt{5}\)
bài 2 : tính
a, \(\sqrt{3+\sqrt{5}}-\sqrt{3-\sqrt{5}}-\sqrt{2}\)
b,\(\left(\sqrt{12}+\sqrt{75}+\sqrt{27}\right):\sqrt{15}\)
c, \(\left(12\sqrt{20}-8\sqrt{200}+7\sqrt{450}\right):\sqrt{10}\)